Antimicrobial stewardship in spinal cord injury: A multidisciplinary approach. (3rd September 2021) - Clarke, Daniel; Nguyen, Daniel; Overton, Kristen
Abstract : Context: In a global environment of escalating antimicrobial resistance and limited new antibiotic development, there is a desire to optimize antibiotic use across all settings to preserve options for the future. Despite this, antibiotics continue to be prescribed inappropriately in many settings. Patients with a spinal cord injury (SCI) are particularly vulnerable to receiving multiple courses of antibiotics, yet there is limited data reviewing antimicrobial stewardship (AMS) programs in this patient population. Hypothesis: Adopting AMS rounds will reduce days of antibiotic treatment. Intervention: We implemented a systematic bedside AMS multidisciplinary team (MDT) ward round within the SCI Unit at our hospital, where a collaborative inter-speciality and inter-professional approach was undertaken to address antibiotic prescriptions. A retrospective audit of antibiotic prescriptions was performed one month prior and one month during the intervention. Outcome measures: An infectious disease consultant led a multidisciplinary, multispecialty ward rounding team, looking at antibiotic appropriateness and guideline compliance. The effectiveness of this intervention was assessed by retrospectively looking at antibiotic days of usage per patient day of occupancy. Results: Antibiotic consumption significantly decreased following the AMS intervention, from 69.8 to 24.3 days on treatment per 100 patient days (P < 0.001). Following implementation of the ward round the proportion of therapeutic guideline compliant prescriptions significantly rose from 18% in April to 56% in August (P < 0.001). Conclusions: Utilizing a collaborative inter-speciality and inter-professional AMS approach and providing face to face feedback about the appropriateness of antibiotic prescribing can help optimize antibiotic usage within a SCI unit.